2009
DOI: 10.1038/aps.2009.99
|View full text |Cite
|
Sign up to set email alerts
|

Transformation of human liver L-O2 cells mediated by stable HBx transfection

Abstract: Aim: To explore the mechanism of hepatocarcinogenesis associated with the hepatitis B virus X protein (HBx), we investigated the role of HBx in transformation using human liver L-O2 cells stably transfected with HBx as a model. Methods: Plasmids encoding HBx were stably transfected into immortalized human liver L-O2 cells and rodent fibroblast NIH/3T3 cells. The expression of alfa-fetoprotein (AFP), c-Myc, HBx, and survivin in the engineered cells was examined by Western blotting. The malignant phenotype of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 45 publications
1
35
0
Order By: Relevance
“…To demonstrate the significance of survivin up-regulation in HBx-induced hepatocarcinogenesis, we successfully generated an engineered cell line model (termed LO2-X-S) that LO2 cells stable transfected with both HBx and survivin. We previously reported that 3 of 8 mice injected with LO2-X cells stably transfected HBx grew tumors [29]. Strikingly, in this study we observed that all 8 mice injected with LO2-X-S cells formed tumors.…”
Section: Discussionsupporting
confidence: 51%
“…To demonstrate the significance of survivin up-regulation in HBx-induced hepatocarcinogenesis, we successfully generated an engineered cell line model (termed LO2-X-S) that LO2 cells stable transfected with both HBx and survivin. We previously reported that 3 of 8 mice injected with LO2-X cells stably transfected HBx grew tumors [29]. Strikingly, in this study we observed that all 8 mice injected with LO2-X-S cells formed tumors.…”
Section: Discussionsupporting
confidence: 51%
“…Despite the absence of a dominant oncogene encoded by HBV genome, HBV X protein (HBx), a key regulatory multifunctional protein of the virus, has been reported to exert a direct hepatocarcinogenic effect in the development of HCC . HBx deregulates a wide variety of host genes related to cell proliferation, cell cycle progress, apoptosis, metastasis, protein degradation pathways, and genetic stability . Previous studies have demonstrated that HBx is able to promote migration and invasion of hepatoma cells by upregulation of many proteins, such as forkhead box protein M1 (FoxM1), OPN, forkhead box protein M1 (FoxM1), MMPs, chemokine [C‐X‐C motif] ligand (MIG), and deregulation of intercellular adhesion …”
Section: Noncellular Component Involving Hcc Metastasismentioning
confidence: 99%
“…We have found that HBx was able to regulate many genes associated with signal transduction pathways, cell cycle, metabolism and proliferation, and this regulation may be involved in the carcinogenesis associated with HBV [21]. Furthermore, in certain contexts, stable HBx transfection resulted in a malignant phenotype in human liver L-O2 cells in vivo and in vitro [22].…”
Section: Introductionmentioning
confidence: 95%